Productivity Growth, Technical Progress, and Efficiency Change in Industrialized Countries - Färe, Rolf; Grosskopf, Shawna; Norris, Mary; Zhang, Zhongyang (American Economic Review, 1994)
This paper analyzes productivity growth in 17 OECD countries over the period 1979-1988. A nonparametric programming method (activity analysis) is used to compute Malmquist productivity indexes. These are decomposed into two component measures, namely, technical change and efficiency change. We find that U.S. productivity growth is slightly higher than average, all of which is due to technical change. Japan's productivity growth is the highest in the sample, with almost half due to efficiency change.